Outcome of gastrointestinal surgery during COVID-19 lockdown in a tertiary care hospital, Nepal (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Perioperative strategies have been changing due to the COVID-19 pandemic to prevent the risk of postoperative complications and transmission of infection. This study was aimed to assess the outcome of gastrointestinal surgery and the risk of transmission by implementing COVID-19 testing criteria and surgical strategy.Method: This was a retrospective descriptive study conducted at the department of surgery at Patan Hospital, Nepal, during COVID-19 lock-down from 24 march to 15 June 2020. All patients who underwent gastrointestinal (GI) surgery were included. High-risk patients (as defined by the Hospital Incident Command System, HICS) were tested for COVID-19 preoperatively. Surgery was performed in COVID operating room with full protective gear. Low-risk patients were not tested for COVID-19 preoperatively and performed surgery in non-COVID OR. Data from patient’s case-sheets were analyzed descriptively for age, gender, comorbidities, hospital stay, RT-PCR results, surgeries, and postoperative complications.Result: There were total 44 GI surgeries performed; 31(70.5%) were emergency, 5(11.3%) semi-emergency and 8(18.2%) oncology. There were 11(25%) patients tested for COVID-19 preoperatively and were negative. Nine HCWs tested for COVID-19 randomly were negative. Severe postoperative complications developed in 3 patients, with one mortality.Conclusion: Among GI surgeries, there was no increase in postoperative complications and transmission of COVID-19 to the patients or HCWs following the implementation of standard testing criteria and surgical strategy.